Point of Care Measurement of Body Mass Index and Thyroid Nodule Malignancy Risk Assessment - Ahmadi, Sara; Pappa, Theodora; Kang, Alex S.; Coleman, Alexandra K.; Landa, Iñigo; Marqusee, Ellen; Kim, Matthew; Angell, Trevor E.; Alexander, Erik K. (Frontiers in Endocrinology, 2022)
Background Large scale epidemiology studies have suggested obesity may increase the risk of thyroid cancer, though no prospective analyses using real-world measurement of BMI at a time proximate to initial thyroid nodule evaluation have been performed. Methods We performed a prospective, cohort analysis over 3 years of consecutive patients presenting for thyroid nodule evaluation. We measured BMI proximate to the time of initial evaluation and correlated this with the final diagnosis of benign or malignant disease. We further correlated patient BMI with aggressivity of thyroid cancer, if detected. Results Among 1,259 consecutive patients with clinically relevant nodules, 199(15%) were malignant. BMI averaged 28.6 kg/m2 (SD: 6.35, range:16.46-59.26). There was no correlation between the measurement of BMI and risk of thyroid cancer (p=0.58) as mean BMI was 28.9 kg/m2 and 28.6 kg/m2 in cancerous and benign cohorts, respectively. Similarly, BMI did not predict aggressive thyroid cancer (p=0.15). While overall nodule size was associated with increased BMI (p<0.01), these data require further validation as obesity may hinder nodule detection until large. Conclusion In contrast to findings published from large scale association studies drawn from national databases, these prospective data of consecutive patients presenting for nodule evaluation detect no association of obesity (as measured by BMI) with thyroid cancer. Real time measurement of BMI at the time of thyroid nodule evaluation does not contribute to cancer risk assessment.